Cambios en los estilos de vida de los estudiantes universitarios de la UNSA y UCSM, durante la pandemia y el retorno a la presencialidad 2020-2022 - Serruto Castillo, Alison (2023)
The aim of this article is to analyze changes in the lifestyles of students at the National University of Saint Augustine (UNSA) and the Catholic University of Santa Maria (UCSM) during the period of the COVID-19 pandemic and the return to face-to-face attendance between 2020 and 2022. For this purpose, a basic, descriptive, and cross-sectional design study was carried out, in which a Likert scale questionnaire was used to collect information on the health, socialization and study habits of students who migrated to return to face-to-face attendance. The study sample consisted of 194 students from both universities located in the city of Arequipa, Peru. The results of this study revealed significant changes in the students' lifestyles during the pandemic and their return to face-to-face mode. Improvements were observed in physical activity, sleep, stress management, socialization and study habits. However, one negative aspect was diet, which was affected during this period. It is important to note that although the lifestyles of the university students were moderately healthy, more positive results were found among the students at the Catholic University of Santa Maria (UCSM). The findings of this study are significant with a p-value of 0.001, indicating that there are clear differences between the two periods.